Early Effects of Hyperbaric Oxygen on Inducible Nitric Oxide Synthase Activity/Expression in Lymphocytes of Type 1 Diabetes Patients: A Prospective Pilot Study - Ivana Resanovic; Zoran Gluvic; Bozidarka Zaric; Emina Sudar-Milovanovic; Aleksandra Jovanovic; Davorka Milacic; Radmilo Isakovic; Esma R. Isenovic (International Journal of Endocrinology)
This study aimed at examining the early effects of hyperbaric oxygen therapy (HBOT) on inducible nitric oxide synthase (iNOS) activity/expression in lymphocytes of type 1 diabetes mellitus (T1DM) patients. A group of 19 patients (mean age: 63 ± 2.1) with T1DM and with the peripheral arterial disease were included in this study. Patients were exposed to 10 sessions of HBOT in the duration of 1 h to 100% oxygen inhalation at 2.4 ATA. Blood samples were collected for the plasma C-reactive protein (CRP), plasma free fatty acid (FFA), serum nitrite/nitrate, and serum arginase activity measurements. Expression of iNOS and phosphorylation of p65 subunit of nuclear factor-κB (NFκB-p65), extracellular-regulated kinases 1/2 (ERK1/2), and protein kinase B (Akt) were examined in lymphocyte lysates by Western blot. After exposure to HBOT, plasma CRP and FFA were significantly decreased (p<0.001). Protein expression of iNOS and serum nitrite/nitrate levels were decreased (p<0.01), while serum arginase activity was increased (p<0.05) versus before exposure to HBOT. Increased phosphorylation of NFκB-p65 at Ser536 (p<0.05) and decreased level of NFκB-p65 protein (p<0.001) in lymphocytes of T1DM patients were observed after HBOT. Decreased phosphorylation of ERK1/2 (p<0.05) and Akt (p<0.05) was detected after HBOT. Our results indicate that exposure to HBO decreased iNOS activity/expression via decreasing phosphorylation of ERK1/2 and Akt followed by decreased activity of NFκB.